Zn‐Metal–Organic Framework Derived Ordered Mesoporous Carbon‐Based Nanostructure for High‐Performance and Universal Multivalent Metal Ion Storage. Issue 41 (11th September 2022) - Zhang, Hong; Wang, Haozhi; Pan, Zhenghui; Wu, Zhong; Deng, Yida; Xie, Jianping; Wang, John; Han, Xiaopeng; Hu, Wenbin
Abstract: Metal–organic framework (MOF) derivatives promise great potential in energy storage and conversion because of their excellent tunability in both the active metal sites, organic links, and the overall structures down to atomic and up to mesoscale. Nevertheless, a big challenge is to precisely control and thoroughly understand the actual MOF‐to‐derivative conversion process to realize the template‐free synthesis of the MOF‐derived ordered mesoporous materials. Here, a class of ordered mesoporous N‐doped carbon nanoflakes is presented with slit‐shaped pores synthesized by one‐step pyrolysis of Zn1 Cu x –MOF, where the Cu doping plays a critically important direction‐inducing function on the dissociation of organic ligands during the pyrolysis. Benefiting from the uniquely ordered mesoporous structure and large specific surface area (910 m 2 g −1 ), the Zn1 Cu x –MOF‐derived ordered mesoporous carbon nanoflakes present outstanding electrochemical storage performance for multivalent metal ions, such as Mg 2+, Ca 2+, Co 2+, Ni 2+, Al 3+, and Zn 2+, demonstrating the universal nature of the slit‐shaped pores in enabling the multivalent metal ions for energy storage. Moreover, the assembled flexible Zn‐ion hybrid supercapacitor (ZHSC) delivers a high specific capacity of 134 mAh g −1 at 0.5 A g −1, excellent cycling and mechanical stability, showing great application potential in the new generation energy storage devices. Abstract : A Cu‐doped Zn–MOF (metal–organic framework) derived orderly mesoporous carbon‐based nanostructure is synthesized by template‐free pyrolysis and the Cu doping presents a direction‐inducing function on the dissociation process of organic ligands during the pyrolysis. This orderly mesoporous derivative provides a fruitful platform to achieve a class of high‐performance electrodes for universal multivalent metal ion storage in aqueous electrolytes.